The Generalizability of the Paediatric Developmental Passport: A Multi-Site Randomized Controlled Trial. (1st June 2016) - Young, E; Aiyadurai, R; Cellupica, U; Jegathesan, T; Dillon, K; Friedman, G; Huber, J; Merchant, S; Minhas, R; Maguire, J
Abstract: BACKGROUND: The Pediatric Developmental Passport (passport) is an innovative tracking tool for families of children with autism spectrum disorder (ASD). It provides a mechanism for clearly communicating appropriate regional developmental services, an opportunity track progress in accessing these developmental services and a valuable summary of the developmental care received by that child for pediatrician. A qualitative study with parents and health professionals (developmental pediatricians, developmental nurses, pediatricians) lead to the design and iterative review of the passport. OBJECTIVES: The objective of this study was to determine the general-izability and effectiveness of the passport compared to placebo in a multi-site pragmatic randomized control trial. DESIGN/METHODS: A pragmatic multi-site randomized controlled trial was conducted with families of children between 0-6 years of age diagnosed with ASD. Families from two different models of developmental care were enrolled into the study. One site was a sub-urban developmental consultation clinic and the second site was a shared-care model between developmental pediatricians and general pediatricians in an urban resource restricted area. All families included in the study were randomized to receive the passport or placebo (blank card). Agencies providing Autism specific behaviour therapy (ABA) within each site were contacted directly to obtain accurate contact and access status of recommended developmental services. To determine passport effectivenes a pearson's chi square test was conducted using a significant p value of <0.05. RESULTS: Forty children with ASD were included and followed in this study. The passport proved to be significantly more effective in aiding families to contact developmental services than the placebo (blank card). A significantly larger portion of families (90.5%) with the passport contacted agencies for ABA (applied behaviour analysis) therapy compared to families with the placebo (61.9%, (p value significant at <0.05). More families with the passport tended to contact ABA in less than 2 months (48%) than the placebo group (35%), but this was not statistically significant. CONCLUSION: The pediatric developmental passport enables families of children newly diagnosed with Autism to contact necessary behavioural services more often than those who did not receive the passport after diagnosis.